Functional Territory of University Education Services in Basrah Province - Azeez Hamid , Assist. Lect. Abather; Mudaffar Shar Al-Kaabi, Assist .Prof.Dr. Murtadha (Basra studies journal, 2023)
The city is a common denominator connect the various types of its functional relations with its regions, this make its influence appear in a growing way and in a way that leads to making the link between them stronger. So that one cannot consider any place as a region without the presence of a central city, for the functional region contributes in general to supplying city's population and the surrounding areas with other cities by services and functions. It can be said that the areas of influence of the city appear in the form of transitional zones rather than in the form of diverging lines. The university career region contributes as a place of attraction that provides central jobs through the spatial space in which it is located. It is not necessary that these functional regions locate on a nearby area, but may go beyond it to areas in contact with it or far from it, and for this reason the research came to shed light on the functional region of University of Basra. For it occupies a central position if it is classified after the University of Baghdad, and the importance came through the administrative, educational and administrative services it provided to the residents of the city of Basra, which is considered the Al-Mamas area in general, and the residents of the rest of the governorates of Iraq in general with a wide regional dimension.